(untitled) (Journal of Imam Al-Kadhim College, 2023)
Abstract :Talking about direct and indirect verbal acts in the pragmatic research literature corresponds to talking about literal interrogation and metaphorical interrogation in the Arab linguistic heritage because if the meaning of the utterance is the same as what the sender wants to achieve in complete conformity, indicating his intent, then it is a direct verbal act, but if it contradicts what the sender wants to achieve, it is an indirect verbal act. Since it was sent indirectly, the sender’s goal was clear in what it meant. The same is true of both literal and metaphorical questioning. The speaker’s freshness of mind (the simultaneous realization of direct and indirect verbs) could be completely divorced from its literal meaning and transformed to signify the speaker’s intended meaning. The deliberative have separated themselves into two groups due to the intense debate that this problem has caused among the masters of deliberation. The other team maintains that the utterance is separated from its original meaning and given a new meaning. Indirectness is using the literal meaning to attain a second meaning through it. Similarly to how the concept of indirect speech action was articulated in broad terms in Arab heritage and how this theory was clearly referenced, With the theory of indirect verbal acts as a guide, this study sought to investigate this aspect of the interrogative style found in the Quranic discourse, as well as demonstrate how this issue is addressed in our exegetical heritage and what the commentators wrote about their interpretation of whether the metaphorical interrogation in the Quranic text retained its literal meaning or was completely detached from it. The purpose of this is to show how they handled this matter.